Semantic Reconstruction of Vocabulary with a Speed Value Derived from Verbs of Object Movement - E. O. Borisova (Научный диалог, 2021)
The article deals with the verbs of moving an object by the subject, developing the semantics of low and high speed of action. The research is mainly based on the vocabulary of Russian folk dialects, but the facts of the literary language are also involved. Several lexical groups are distinguished, within which “speed” meanings can develop, depending on the way of movement indicated by the verbs: without lifting off the ground; by the strength of your movement; by air; appropriation; giving away; putting into something. Within each group, the main models of the development of lexemes with the semantics of speed, determined by the features of the called action, the meaning of affixes and possible associative series are described. It is found that, although the movement of an object by a subject is a fairly extensive lexical group, a limited set of models are presented directly in the designation of speed, which are implemented using synonymous verbs (tyanut’ [pull], tashchit’ [drag] and volochit’ [crawl along]; brosat’ [throw], kidat’ [cast] etc; khvatat’ [grab] etc.). The correlations of the semantics of speed with other semantic fields that arise within the framework of this thematic group are described.